Development of a Weight-Faltering Flyer as a Strategy to Strengthen Stunting Prevention - Nabihah, Asma Syifa; Abbas, Hafid; BRD, Henny Herawati; Tijari, Ahmad; Parinduri, Fitri Khoiriyah (Newinera Publisher, 2025)
Stunting remains a major public health challenge in Indonesia. Educational interventions through visual media such as flyers show promise in improving understanding of early detection of weight faltering, yet many existing materials are not designed participatorily nor tailored to local contexts. To develop, pilot, and evaluate the effectiveness of a weight-faltering–based flyer in improving mothers’ knowledge on stunting prevention in Sukaharja Village. This study employed a Research and Development (R&D) design with a mixed-methods approach. The stages included: an FGD to identify learning needs, media design by a multidisciplinary team, expert validation, limited field testing, and impact evaluation using a quasi-experimental design with two groups (flyer intervention vs. lecture control), each consisting of 20 mothers. Data were collected through pre-test and post-test assessments as well as in-depth interviews. Data analysis was conducted using a convergent approach integrating quantitative and qualitative findings. The FGD revealed low community understanding of weight faltering. The developed colored A4 flyer included growth charts, stunting risk indicators, complementary feeding guidelines, and encouragement to visit the posyandu. The trial showed that 90% of respondents agreed on the clarity and attractiveness of the media. Impact evaluation demonstrated a significant increase in the knowledge scores of the flyer group (76.0 → 78.5; p = 0.043), while the lecture group showed no significant improvement (73.0 → 73.5; p = 0.480). Follow-up interviews revealed positive shifts in attitudes and behavioral intentions regarding monitoring children’s growth and development.